Pengaruh Kesehatan dan Keselamatan Kerja (K3) dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Kutalaga Jaya Abadi Kota Sawahlunto - April, Muhammad; Husnaidi, Arfan (Jurnal Rumpun Ilmu Ekonomi, 2024)
This study looks into the relationship between occupational health and safety (OHS), pay, and employee performance at PT Kutalaga Jaya Abadi. With the use of questionnaires, documentation, and interviews, data is gathered quantitatively. Purposive sampling was used to select the sample, and 47 respondents were included. Data analysis using multiple linear regression with traditional assumption tests and hypothesis testing was conducted using the SPSS 26 software. The results showed that employee performance is positively and significantly impacted by Occupational Health and Safety (OHS). Employee performance is positively impacted by compensation as well. The study's findings demonstrated the simultaneous effects of remuneration and occupational health and safety (OHS) on worker performance. Additionally, there is a direct correlation between worker performance (Y) and Occupational Health and Safety (OHS) (X1) and Compensation (X2).